Cytotoxicity of Qualea grandiflora Mart. leaf extract (Vochysiaceae) on pre-osteoblast culture. Evaluation of cell viability and expression/activity of MMPs - Tokuhara, Cintia Kazuko (2016)
The use of medicinal plants with the purpose of treatment of many diseases is common. However, a scientific study to ensure the doses considered safe for consumption is required. Qualea grandiflora has been used in folk medicine to treat bloody diarrhea and nervous system depressant, antioxidant and anti-inflammatory activity and among other applications. The aim of this study was to investigate the influence of hydroalcoholic extract obtained from the leaves of Q. grandiflora on MC3T3-E1 pre-osteoblast lineage, correlating the effects of this plant on cell viability and expression and activity of matrix metalloproteinase. It was performed using serial dilution (1000 g/mL, 100 g/mL, 10.0 g/mL, 1.0 g/mL and 0.1 g/mL) of different concentrations of the hydroalcoholic extract of leaves Qualea exposed on preosteoblast MC3T3-E1 cell line. Four periods (24, 48, 72 and 96 h) were stipulated in order to assess cytotoxicity of the plant. From these safe concentrations were chosen (10.0 g/mL, 1.0 g/mL and 0.1 g/mL) and evaluated the expression and activity of MMPs of these cells exposed to the extract Qualea. We found in 70% EtOH extract of the leaves of Q. grandiflora, is mostly derived from gallic acid compounds and other compounds of flavonoid. From the concentrations evaluated, only the lower concentrations (0.1 g/mL, 1.0 g/mL and 10.0 g/mL) showed not be cytotoxic to this cell line and for concentrations higher than 10.0 g/mL caused decreased cell viability. An increase in MMP-9 expression in the group with the extract was found, though the activity was not confirmed by zymography assay. In conclusion, our results indicate what is already practiced by folk medicine as low extract concentrations shown to be safe for this cell line, but high concentrations showed cytotoxicity.